Effects of the Operational Parameters in a Coupled Process of Electrocoagulation and Advanced Oxidation in the Removal of Turbidity in Wastewater from a Curtember - Paul Alcocer-Meneses; Angel Britaldo Cabrera-Salazar; Juan Taumaturgo Medina-Collana; Jimmy Aurelio Rosales-Huamani; Elmar Javier Franco-Gonzales; Gladis Enith Reyna-Mendoza (Applied Sciences, 2022)
The tannery industry during its process generates various polluting substances such as organic matter from the skin and chemical inputs, producing wastewater with a high concentration of turbidity. The objective of this research is to evaluate the most appropriate operational parameters of the coupled process of electrocoagulation and advanced oxidation to achieve the removal of turbidity in wastewater from a tannery in the riparian zone (tannery). This process uses a direct current source between perforated aluminum electrodes of circular geometry submerged in the effluent, which causes the dissolution of the aluminum plates. For our study, an electrocoagulation unit coupled to an ozone generator has been built at the laboratory level, where the influence of five factors (voltage, inlet flow to the reactor, initial turbidity, pH, and ozone flow) has been studied with three levels with regarding turbidity, using the Taguchi experimental methodology. The optimal conditions for the removal of turbidity were obtained at 10 volts, 7.5 pH, 360 L/h of wastewater recirculation flow rate; 2400 mg/h of ozone flow rate; and 1130 NTU of initial turbidity of the sample in 60 min of treatment reaching a removal of 99.75% of the turbidity. Under optimal conditions, the removal of chemical oxygen demand (COD) and biochemical oxygen demand (BOD) was determined, reaching a removal percentage of 33.2% of COD and 39.36% of BOD was achieved. Likewise, the degree of biodegradability of the organic load obtained increased from 0.467 to 0.553.